2014
DOI: 10.1007/s00726-014-1781-4
|View full text |Cite
|
Sign up to set email alerts
|

Methionine deficiency reduces autophagy and accelerates death in intestinal epithelial cells infected with enterotoxigenic Escherichia coli

Abstract: Infections by enterotoxigenic Escherichia coli (ETEC) result in large economic losses to the swine industry worldwide. Dietary supplementation with amino acids has been considered as a potential mechanism to improve host defenses against infection. The goal of this study was to determine whether methionine deprivation alters ETEC interactions with porcine intestinal epithelial cells. IPEC-1 cells were cultured in media with or without L-methionine. Methionine deprivation resulted in enhanced ETEC adhesion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…Bama mini-pigs had higher (P < 0.05) mRNA levels for LAT1, SNAT2, and EAAC1, but a lower (P < 0.05) mRNA level for PepT1, compared with Landrace pigs. Collectively, our synthesis in cells and signaling molecules (Wu et al , 2012(Wu et al , b, 2015Li et al 2011;Wang et al 2014aWang et al , b, 2015a but also regulators of gene expression (He et al 2013;Chen et al 2014;Zhang et al 2013;Ren et al 2013aRen et al , b, c, 2014aTan et al 2011;Yang et al 2013;Feng et al 2014;Tang et al 2014Kong et al 2014) and protein posttranslational regulation . Additionally, AAs are key precursors for the biosynthesis of hormones and low-molecular-weight nitrogenous substances (Wu 2013a, b).…”
Section: Introductionmentioning
confidence: 96%
“…Bama mini-pigs had higher (P < 0.05) mRNA levels for LAT1, SNAT2, and EAAC1, but a lower (P < 0.05) mRNA level for PepT1, compared with Landrace pigs. Collectively, our synthesis in cells and signaling molecules (Wu et al , 2012(Wu et al , b, 2015Li et al 2011;Wang et al 2014aWang et al , b, 2015a but also regulators of gene expression (He et al 2013;Chen et al 2014;Zhang et al 2013;Ren et al 2013aRen et al , b, c, 2014aTan et al 2011;Yang et al 2013;Feng et al 2014;Tang et al 2014Kong et al 2014) and protein posttranslational regulation . Additionally, AAs are key precursors for the biosynthesis of hormones and low-molecular-weight nitrogenous substances (Wu 2013a, b).…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, more than 80 amino acids were identified in meteorites such as Murcheson and the Lonewolf Nunataks 94102 (Kvenvolden et al 1970;Cronin & Chang 1993;Glavin et al 2006;Elsila et al 2007). A detailed isotopic analysis (D/H; N) provided compelling evidence that these molecules were formed in the ISM (Robert & Epstein 1982;Yang & Epstein 1983;Cronin & Chang 1993;Alexander et al 1998). However, with the exception of formamide (HCONH 2 ; Jones et al 2011), the underlying formation mechanisms of the COM carrying the peptide bond are far from being understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown MSRA and MSRB were involved in the regulation of mitochondrial function [29], leading to alterations in autophagy function [30]. Furthermore, Tang and colleagues observed that MSR reduction caused autophagy inactivation and accelerated cell death [30].…”
Section: Discussionmentioning
confidence: 97%